THE ROLE OF TOUR OPERATORS IN THE SYSTEM OF ECONONOMIC RELATIONS - Ashurova , Maftuna Sharifovna (Educational Research in Universal Sciences, 2023)
According to the World Travel & Tourism Council, the contribution of the tourism industry to the world economy in 2022 will be 8.6 trillion dollars[1], which is only 6.4% behind the level before the pandemic. Of course, the activity of the tour operator also has its own contribution, and it has its place in tourism as an economic lever. [1] https://wttc.org/Portals/0/Documents/Reports/2022/EIR2022-Global%20Trends.pdf